(untitled) (Práxis Educativa, 2024)
This article aims to discuss the meanings, flows, and movements of changes in postgraduate evaluation policy in the period 2017-2020, based on the recommendations for improving the model by the Monitoring Committee of the 2011-2020 National Postgraduate Studies Plan. This text is the result of broader research on the topic and is based on a documentary study that analyzes texts produced by the Commission/Coordination for the Improvement of Higher Education Personnel (CAPES) and the Education Area Commission, in response to recommendations. As a theoretical and methodological guideline, the Theory of Policy Enactment proposed by Ball, Maguire and Braun (2016) was adopted, which understands policy as a space for negotiation, creation of meanings, contestation, and struggles between different actors. The results reveal a complex movement of negotiations and renegotiations around the evaluation policy, with different flows of actors and forces being debated in the area committees, in scientific societies and in the program coordinations. Keywords: Assessment policy. Postgraduate studies. Education.